HUBUNGAN ANTARA KONSUMSI AIR KELAPA MUDA DENGAN PENINGKATAN HEMOGLOBIN PADA IBU POST PARTUM DI BPM SUPARMI SITORUS - Br. Naibaho, Samini; Samsinar, Samsinar; Salyani, Salyani; Paninsari, Debora (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
One of the complications that occurs during the post partum period is bleeding caused by anemia in the mother. Anemia is based on Hemoglobin (Hb) levels in the body. If the Hb level in a pregnant woman's body is lower than the normal value, namely 11gr/dl, then excessive blood thinning can occur during delivery, which can result in bleeding. This research uses a quasi- experimental research method, namely a method used to look for the effect of certain treatments against other variables under controlled conditions. In this study, it was divided into two groups, namely the control group which was not given young coconut water to postpartum mothers, and the experimental group which was given young coconut water to postpartum mothers. Most of the mothers in the intervention group experienced an increase in postpartum hemoglobin levels, the number reached 14 mothers (70%) from a total of 20 post partum mothers' data were taken. Meanwhile, in the control group, there was a decrease in hemoglobin levels in the majority of mothers, the number reached 9 mothers (45%) from a total of 20 post partum mothers' data taken at BPM Suparmi Sitorus. The results of the chi-square test found a p-value of 0.001 with an ? error rate of 0.005. From these results, it is concluded that the p-value of 0.001 is smaller than the error rate of 0.005. Therefore, it can be concluded that (Hi) is accepted and (H0) is rejected. This shows that there is a relationship between consumption of young coconut water and increased hemoglobin in post partum mothers at BPM Suparmi Sitorus.